Harnessing Fe3O4 Screen-Printed Modified Electrode Sensor for Detecting Epinephrine in Buff Orpington Rooster and Rhodes Island White Broiler - Fayemi, Omolola E.; Elugoke, Saheed E.; Dina, Oluwole; Mwanza, Mulunda; Fayemi, Peter O. (Frontiers in Sensors, 2022)
Nano-scale detection and characterization of neurotransmitters from real samples is a novel analytical technique with multiple applications in the field of nano-biotechnology. This in-situ electrochemical sensing tool has growing advantages of high reproducibility, rapid response, superior sensitivity, selectivity, accuracy, and miniaturization. A screen-printed iron oxide (Fe3O4) modified electrode was harnessed in this study for detecting epinephrine (EP), a chemical messenger or signalling neuro transmitting molecule, from two breeds of chickens. The fabricated sensor was used for the analysis of EP in the real and unspiked samples. UV-visible spectroscopy, Fourier-Transform infrared spectroscopy (FT-IR), Transmission Electron Microscopy (TEM), and Scanning Electron Microscopy (SEM) were used for characterizing the surface of nanoparticles prior to modification of screen-printed silver electrode (SPSE). The XRD diffractogram of Fe3O4 nanoparticles showed peaks at 30.1°, 35.7°, 43.3°, 53.9°, 57.5°, and 63.0°, corresponding to Miller indices of 220, 311, 400, 422, 511, and 440, respectively. This diffraction pattern indicates that the Fe3O4 nanoparticles have a spinel structure. Simultaneous detection of EP in the presence of ascorbic acid was obtained from Fe3O4 electrode. Further result shows a corresponding rise in oxidation peak current (Ipa) of EP with an increase in its concentration and scan rate of 25–400 mVs−1 confirming catalytic properties of the modified electrode towards EP. Our findings demonstrate that the fabricated sensor used for detecting EP in blood serum, breast muscle, and visceral organs of both chicken breeds produced better recovery.